ANALISA KELAYAKAN INVESTASI USAHA PEMBENIHAN IKAN DI BALAI BENIH IKAN (BBI) LOKAL KABUPATEN KUBU RAYA - Taufik, M.; Muani, Ani; ., Radian (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2013)
Business Investment Feasibility Analysis of Fish Hatchery in Local Fish Breeding Center (BBI) of Kubu Raya Regency. Development of freshwater fish farming in Kubu Raya regency is highly depends on the availability of qualified fish seed, since it is the input for the fish farmers. In relation with the provision of qualified fish seeds, the local government through the Department of Fisheries and Marine has build a local fish breeding center (BBI) in Kubu Raya regencyas aunit that produces qulified fish seed. It aimstomeet the needs of fish seed in Kubu Raya, so that may contribute toan increase in local revenue (PAD). The objective of this researchare: to analyze the demand of the type and the amount of fish seeds in Kubu Raya regency, how muchfish seeds produced in accordance with the capacity of facilities and infrastructure in BBI;to analyze the feasibility of a fish hatchery business investments, how much profit sobtained compared to costs incurred by local governments which can contribute to the increased of PAD; and to analyze the sensitivity of investment feasibility fish hatchery operations in the event of changes in the factors that may affect the benefits and costs . This research was conducted by using a qualitative descriptive and Microsoft Excel program to assess the feasibility of business investment in fish hatchery local BBI of Kubu Raya regency. Based on the analysis of fish seed demand in Kubu Raya regency, namely 4.084 million seed catfish, 2.776 million tilapia and 808.640 carp, while in West Kalimantan fish seed requirement are 36,106,560 catfish, 20,913,680 tilapia and 20,482,880 carp. Fish seed production capacity in local BBI of Kubu Raya Regency is 2.288 million seed catfish, 1.884 million seed tilapia and 1.055 million seedcarp. The results of the feasibility analysis of business investment in fish hatchery local BBI of Kubu Raya regency shows NPV = 4,698,084, Net B/C 1.19, IRR 16.17% and PBP 5 years 1 month with10 years project duration, and thus the investment business in fish hatchery local BBI of Kubu Raya regencyis feasible. Sensitivity analysis shows that if there is an increase of production costs (feed, fertilizer, lime and drugs) of 7.62%, the value of profitability NPV = 4,575,511, net B/C 1.101, IRR 16, 11%, and PBP 5 years 6 months. In conclusion, business investment of fish hatcheries in local BBI Kubu Raya regency is feasible. Keywords : Demand seeds , investment feasibility, fish hatchery, Local BBI .